Preventing microbe colonization on avocado (Persea nubigena var. guatemalensis) through metabiotic treatment, a promising postharvest safety improvement - Tenea, Gabriela N.; Angamarca, Evelyn; Cifuentes, Victor; Hidalgo, Jazmin (Frontiers in Microbiology, 2024)
Lactic acid bacteria (LAB) produce various metabolites (i.e. metabiotics) with inhibitory capacity towards harmful foodborne pathogens. This study aimed to design several antimicrobial formulations based on metabiotics obtained from different native LAB species (Lactobacillus pentosus UTNGt5, Lactococcus lactis UTNGt28, and Weissella cibaria UTNGt21O) and to detect the possible mode of action towards two multi-drug resistant Staphylococcus spp. strains isolated from avocado (Persea nubigena var. guatemalensis) fruits. Additionally, the formulation with the highest inhibitory activity was tested ex vitro on avocados at the immature (firm) ripeness stage to evaluate their effect on microorganisms' growth and fruit quality attributes postharvest. Out of the top five formulations showing the highest bactericidal effect in vitro at their minimum inhibitory concentration (1 x MIC) on both Staphylococcus spp. targets one candidate annotated P11 (consisting of UTNGt21O and UTNGt28; 1:3, v/v) was selected. Co-cultivation of Staphylococcus strains with P11 formulation results in cell viability reduction by 98%, by impairing the integrity of the cell membrane inducing cytoplasm molecule content leakage, protein profile changes, and finally bacterial death. Even though the total coliforms, Staphylococcus spp., Enterobacter spp., molds, and yeasts counts were not fully eliminated by day 13 of storage, a statistically significant reduction (p < 0.05) in viable cell counts were observed by day 8 upon the P11 treatment compared with non-treated control (C) and treated with a commercial disinfectant (T1) samples, suggesting that P11 formulation inhibited microbial colonization during storage. Likewise, no visible dark spots were observed on the mesocarp (pulp) upon the treatment with P11, whereas T1 and C fruits showed greater dark spots on the pulp as indicative of damage. The quality attributes, such as pH, total soluble solids, total titratable acidity, antioxidant capacity, and total polyphenol content, were not affected by the treatment. Principal Component Analysis (PCA) conducted on these five variables showed a clear separation of samples according to the maturity stage regardless of the treatment. These results suggest that the active metabolites from LAB strains might create a barrier between the exocarp and mesocarp, inhibiting the microorganisms colonization, reducing fruit damage, and lengthening the fruit quality and safety postharvest.